MEREFORMASI KONSEP PARATE EXECUTIE TERHADAP OBJEK HAK TANGGUNGAN YANG MENJAMIN KEPASTIAN HUKUM, KEADILAN, KEMANFAATAN - Alvin Ramadhan Nur Luis (Proceeding International Conference on Social Sciences, 2026)
One way to enforce a debt security is through parate executie, which involves selling the debtor’s mortgage under their own power without obtaining a fiat from the Chief Justice. In practice, parate executie does not meet the legal requirements, as it isi considered an un lawfull act. Consequently, creditors are deprived of convenience, legal certainty, justice and benefits. This study aims to reform the concept of parate executie for mortgages, which provides legal certanty, justice and benefits for creditors. This study primarily employs normative legal research methods, empolying a statute approach and a case approach. The finding indicate that the obstacles to emplementing parate executie are objective weaknesses, namely inconsistent statutory provisions and inconsistent interpretations of parate executie implementation, which subsequently lead to court decisions, jurisprudence, and the supreme Court’s circular letter (SEMA) requiring execution by court fiat. The next obstacle is the subjective weakness, namely that creditors often do not immediately collect debts so that the amount of debt is getting bigger, and the next subjective weakness is the frequent resistance from the debtor. That is whay there is a need for a reforms of the concept of parate execution of mortgage rights on land based on the values of legal certainly, justice and benefit which is carried out by repositioning the main objective of implementing parate execution, namely providing convenience for creditors throught the placement and fulfillment of the rights and obligation of the parties as the main objective, as well as revitalizing the legal aspect through synchronization of statutory regulations, and fulfilment of implementing regulations.